2013
DOI: 10.1093/trstmh/trt001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for tuberculosis in HIV-infected patients while on antiretroviral treatment in Cambodia

Abstract: The incidence of early TB was high, and predominantly associated with advanced HIV progression markers. Earlier ART initiation and enhanced TB screening prior to and after ART initiation is warranted. Late TB amounts to almost half of the total TB burden, meriting specific preventive and diagnostic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
3
18
1
Order By: Relevance
“…All care was provided by physicians. More information on the program has been published before [15][17].…”
Section: Methodsmentioning
confidence: 99%
“…All care was provided by physicians. More information on the program has been published before [15][17].…”
Section: Methodsmentioning
confidence: 99%
“…The risk of TB in HIV‐positive persons has been extensively reviewed . Its reported association with one's immunological status, as reflected by CD4 count and advanced CDC stage (or acquired immune deficiency syndrome (AIDS) stage), was confirmed in studies in African and Asian countries including Ethiopia, China and Cambodia . Other risk factors include smoking, silicosis and recent contacts with TB transmitters who may not be HIV‐infected .…”
Section: Disease Burden Of Tb/hiv Co‐infectionsmentioning
confidence: 99%
“…5 Its reported association with one's immunological status, as reflected by CD4 count and advanced CDC stage (or acquired immune deficiency syndrome (AIDS) stage), was confirmed in studies in African and Asian countries including Ethiopia, 6 China 7 and Cambodia. 8 Other risk factors include smoking, silicosis and recent contacts with TB transmitters who may not be HIV-infected. 5 Sociodemographic characteristics also play a role, as reflected by a higher incidence in occupations with higher TB prevalence, for example, miners, and immigrants from higher prevalence countries, and people who use drugs.. 9,10 Male gender was associated with TB/HIV co-infection, reflecting the gender association in TB generally.…”
Section: Disease Burden Of Tb/hiv Co-infectionsmentioning
confidence: 99%
“…Besides, studies has also found that, the lower base line CD4 cell count and at advanced WHO staging of HIV of individuals also contributes to the development of TB among PLHIV [10,12,[18][19][20][21][22][23]. Furthermore lower base line hemoglobin level (<12 g/dl) and base line Body Mass Index (BMI) less than 18.5 kg/m 2 was also shown to have an association with TB infection [18,21,23,24]. Sociodemographic factors have association with TB infection In addition to clinical factors.…”
Section: Introductionmentioning
confidence: 99%